Growth as Constraint - Cobley, Paul (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2018)
Human modelling is unique among the modelling of all the animals because it features both nonverbal and verbal communication. Yet, in the development of this modelling, something must be lost with the movement to one mode from another. Biosemiotics, positing ‘semiotic freedom’, claims the organism ‘builds’ on its relation to the environment. This paper will consider the theoretical approaches in biosemiotics which suggest freedom of, repression within and constraints on (in Deacon’s sense) organismic action. The paper aims to stimulate discussion regarding which conceptions and terminology are most appropriate in this sphere.